Diagnostic Accuracy of Natriuretic Peptides for Heart Failure in Patients with Pleural Effusion: A Systematic Review and Updated Meta-Analysis. - Zhi-Jun Han; Xiao-Dan Wu; Juan-Juan Cheng; Shi-Di Zhao; Ming-Zhu Gao; Hong-Yu Huang; Bing Gu; Ping Ma; Yan Chen; Jun-Hong Wang; Cheng-Jian Yang; Zi-He Yan (PLoS ONE, 2015)
Background Previous studies have reported that natriuretic peptides in the blood and pleural fluid (PF) are effective diagnostic markers for heart failure (HF). These natriuretic peptides include N-terminal pro-brain natriuretic peptide (NT-proBNP), brain natriuretic peptide (BNP), and midregion pro-atrial natriuretic peptide (MR-proANP). This systematic review and meta-analysis evaluates the diagnostic accuracy of blood and PF natriuretic peptides for HF in patients with pleural effusion. Methods PubMed and EMBASE databases were searched to identify articles published in English that investigated the diagnostic accuracy of BNP, NT-proBNP, and MR-proANP for HF. The last search was performed on 9 October 2014. The quality of the eligible studies was assessed using the revised Quality Assessment of Diagnostic Accuracy Studies tool. The diagnostic performance characteristics (sensitivity, specificity, and other measures of accuracy) were pooled and examined using a bivariate model. Results In total, 14 studies were included in the meta-analysis, including 12 studies reporting the diagnostic accuracy of PF NT-proBNP and 4 studies evaluating blood NT-proBNP. The summary estimates of PF NT-proBNP for HF had a diagnostic sensitivity of 0.94 (95% confidence interval [CI]: 0.90-0.96), specificity of 0.91 (95% CI: 0.86-0.95), positive likelihood ratio of 10.9 (95% CI: 6.4-18.6), negative likelihood ratio of 0.07 (95% CI: 0.04-0.12), and diagnostic odds ratio of 157 (95% CI: 57-430). The overall sensitivity of blood NT-proBNP for diagnosis of HF was 0.92 (95% CI: 0.86-0.95), with a specificity of 0.88 (95% CI: 0.77-0.94), positive likelihood ratio of 7.8 (95% CI: 3.7-16.3), negative likelihood ratio of 0.10 (95% CI: 0.06-0.16), and diagnostic odds ratio of 81 (95% CI: 27-241). The diagnostic accuracy of PF MR-proANP and blood and PF BNP was not analyzed due to the small number of related studies. Conclusions BNP, NT-proBNP, and MR-proANP, either in blood or PF, are effective tools for diagnosis of HF. Additional studies are needed to rigorously evaluate the diagnostic accuracy of PF and blood MR-proANP and BNP for the diagnosis of HF.